Pengaruh Variasi Arus Pada Pengelasan SMAW Terhadap Uji Kekuatan Bending dan Struktur Micro Baja ST 42 - Mabrullah, Riki Alan; Kosjoko, Kosjoko; Shofiyah, Rohimatush (Indonesian Journal Publisher, 2024)
This research aims to analyze the effect of variations in welding current on the mechanical strength of ST 42 steel using the SMAW welding method and E6013 electrodes with a diameter of 3.2 mm. The variations in welding current used are 90A, 100A and 110A. The tensile test results show that a welding current of 110A produces the highest tensile test value with a yield point (YP) of 8,368 MPa, maximum stress (MAX) of 9,890 MPa, and break point (BREAK) of 5,283 MPa. Bending tests indicate that a welding current of 110A produces the highest bending strength of 10.118 MPa. Microstructural observations revealed that the highest percentage of pearlite was present in welding with a current of 110A, which contributed to an increase in the tensile strength of the material. From the results of this research, it can be concluded that the increase in welding current is directly proportional to the increase in the mechanical strength of ST 42 steel